2013
DOI: 10.3171/2013.1.peds12120
|View full text |Cite
|
Sign up to set email alerts
|

Skull base surgery for tumors in children: long-term clinical and functional outcome

Abstract: Object Skull base tumors in children are rare but require complex approaches with potential morbidity to the developing craniofacial skeleton, in addition to tumor-related morbidity. Reports of long-term clinical and functional outcome following skull base approaches in children are scarce. The authors report long-term outcome in children with tumors undergoing multidisciplinary skull base surgery. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Pediatric skull base tumors are rare and consist of a variety of histology types . Malignant tumors account for 27% to 54% of all pediatric skull base tumors, of which sarcoma is the most common type .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric skull base tumors are rare and consist of a variety of histology types . Malignant tumors account for 27% to 54% of all pediatric skull base tumors, of which sarcoma is the most common type .…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in treatment for pediatric skull base tumors; thus, they are a challenge for oncologists, pediatric surgeons, and radiation practitioners. Multidisciplinary therapy, including surgery, radiotherapy, and chemotherapy, has become a treatment modality for pediatric skull base tumors . However, children are known to be more sensitive to radiation‐induced malignancies than adults by a factor of more than 10 times, and long‐term radiotherapy‐related complications, such as facial growth disorders and dental abnormalities in pediatric patients, have been frequently reported .…”
Section: Discussionmentioning
confidence: 99%
“…This has the potential for brain injury with resultant encephalomalacia and long‐term cognitive changes. A 2013 study by Hayhurst et al evaluated the long‐term functional and cognitive outcomes using the Late Effects Severity Score (LESS) of pediatric patients who had undergone open skull base tumor resection . Eight of 23 patients had elevated LESS scores, indicating late neurologic, endocrine, visual/auditory, or other effects with long‐term follow‐up (average 60 months).…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate was 87% and the rate of permanent neurologic morbidity was 9%. 84 In another series of 26 cases of skull base tumors, a 30.7% complication rate of permanent deficits was reported, with a 92% complete resection rate and 81% tumor-free survival rate at 2 years postoperatively. 2 A retrospective series of 67 children operated for skull base pathologies during a 6-year period 85 reported that 80% of children were alive and well after 2½ years, with no severe postoperative complications.…”
Section: ■ ■ Surgical Approaches In the Pediatric Skull Basementioning
confidence: 94%
“…3 • Even if skull base tumors in children are more aggressive, minimal surgical-related morbidities and good long-term tumor control have been reported. 2,70,83,84 Outcomes • In a series of 55 children who underwent skull base approaches, a 11% rate of permanent neurologic morbidity was reported. 70 • In a series of 23 pediatric patients who underwent skull base approaches for resection of tumors with a median follow-up of 60 months, gross total resection was achieved in 52%.…”
Section: ■ ■ Surgical Approaches In the Pediatric Skull Basementioning
confidence: 99%